ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DITINJAU DARI MINAT BELAJAR SISWA PADA PEMBELAJARAN DARING DIMASA PANDEMI COVID 19 - Roslian Lubis; Muhammad Syahril Harahap; Pia Paramita Tarihoran (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
The aims of this study is to describe students’ mathematical communication ability in term of learning interest in learning online during the Covid-19. The approach of the research used qualitative descriptive with 11 students and 1 mathematics teacher at the eighth grade students as the subject of the research which taken by using purposive sampling technique. Questionnaire, test, and interview were used in collecting the data. The result of the research shows average of students’ mathematical communication ability 57.48 (average category) and average of students’ learning interest is 70.36 (good category). Furthermore, the result of the research shows students’ learning interest is high then students’ mathematical communication ability is high, students’ learning interest is average then students’ mathematical communication ability is average, students’ learning interest is low then students’ mathematical communication ability is low.